Family Businesses: Can the Family and the Business Finances Be Separated? Preliminary Results - George W. Haynes; Rosemary J. Avery (Journal of Entrepreneurial and Small Business Finance, 1996)
Small businesses had nearly 1.25 trillion in loans outstanding from commercial lenders, business finance companies, other businesses in the form of trade credit, and friends and relatives in the early 1990s (Ou, 1991). Based on recent information derived from the National Survey on Small Business Finance (NSSBF), loans held by commercial banks and family members or owners of the firm were significant sources of credit, comprising 54 and 18 percent of all loans, respectively (Haynes, 1996). The relative importance of these types of loans suggests that the finances of the business and the family are often intertwined. This study utilizes the recently released Survey of Consumer Finances to examine the impact of small business ownership on the household's debt structure.
Keywords: G32; 650; Family Firm; Family Business; Co-mingling